2017
DOI: 10.1038/s41598-017-10093-8
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide dynamics in subcellular compartments of malaria parasites using genetically encoded redox probes

Abstract: Redox balance is essential for the survival, growth and multiplication of malaria parasites and oxidative stress is involved in the mechanism of action of many antimalarial drugs. Hydrogen peroxide (H2O2) plays an important role in redox signalling and pathogen-host cell interactions. For monitoring intra- and subcellular redox events, highly sensitive and specific probes are required. Here, we stably expressed the ratiometric H2O2 redox sensor roGFP2-Orp1 in the cytosol and the mitochondria of Plasmodium falc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 73 publications
(90 reference statements)
2
15
0
Order By: Relevance
“…Using a genetically-encoded, mitochondria-targeted GFP-fusion redox probe, we found substantial oxidation following 4h or 24h of DHA treatment, which greatly exceeded any oxidative effect of the cytochrome bc1 inhibitor ATQ or the hemozoin inhibitor CQ. These results agree with earlier studies that also showed an impact of ART derivatives on redox potential in the parasite cytosol [56,83,84]. Further studies are merited to elucidate the role of the mitochondria in both DHA action and K13-mediated resistance.…”
Section: Plos Pathogenssupporting
confidence: 92%
“…Using a genetically-encoded, mitochondria-targeted GFP-fusion redox probe, we found substantial oxidation following 4h or 24h of DHA treatment, which greatly exceeded any oxidative effect of the cytochrome bc1 inhibitor ATQ or the hemozoin inhibitor CQ. These results agree with earlier studies that also showed an impact of ART derivatives on redox potential in the parasite cytosol [56,83,84]. Further studies are merited to elucidate the role of the mitochondria in both DHA action and K13-mediated resistance.…”
Section: Plos Pathogenssupporting
confidence: 92%
“…Recently, it was shown that the dynamics of hydrogen peroxide are also affected by ML304. Employing stable integration of the H 2 O 2 redox probe roGFP2-Orp1 into blood stages of NF54- attB , ML304 was found to significantly increase the cytosolic H 2 O 2 levels [48]. It can, therefore, be deduced that inhibition of the G6PD reaction, likely followed by impairment of NADPH fluxes, markedly affects antioxidant capacity in Plasmodium parasites.…”
Section: Discussionmentioning
confidence: 99%
“…The CQ-sensitive P. falciparum 3D7 and NF54- attB strains were cultured as described in [47, 48], respectively. Briefly, the strains were propagated in red blood cells (RBCs) (A+) in RPMI 1640 medium supplemented with 0.5% w/v Albumax, 9 mM glucose, 0.2 mM hypoxanthine, 2.1 mM l -glutamine, 25 mM HEPES, and 22 µg mL −1 gentamycin at 3.3% haematocrit and 37 °C in a gaseous mixture consisting of 3% O 2 , 3% CO 2 , and 94% N 2 .…”
Section: Methodsmentioning
confidence: 99%
“…However, one important factor to limit radiotherapeutic efficacy is that intracellular microenvironment of most solid tumors is significantly hypoxic [ 6 , 7 , 8 ]. In order to overcome tumor hypoxia, many researches depend on transporting radiosensitizers, such as O 2 , reactive oxygen species (ROS), and radiosensitive drugs (such as bleomycin [ 9 ], topotecan [ 10 ], artemisinin [ 11 ], etc.) to the tumor hypoxic regions by the drug delivery system (DDS) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%